GAMIFICATION IN EDUCATION: ENHANCING ENGAGEMENT AND LEARNING OUTCOMES - Norboboyeva Saida Azamatovna (Bright Mind Publishing, 2025)
In recent years, gamification has become a widely discussed and increasingly applied strategy in modern education. Its central idea is to incorporate game-like principles into learning environments to boost student motivation and engagement. This article explores the theoretical foundations of gamification, its psychological influence on learners, and practical ways it is being used in contemporary classrooms. The benefits, challenges, and recommendations for effective implementation are examined to provide educators with a clearer understanding of how gamification can meaningfully transform the learning experience.
Keywords: Gamification, learner engagement, motivation, educational technology, instructional design.